RESEARCH BACKGROUND OF MOTIVATION IN LANGUAGE LEARNING AND TEACHING - Rustamova Adash Eshankulovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The exploration of motivation in the context of second language acquisition has been ongoing for several years. Dornyei (1990) identifies it as a significant research area following the comprehensive summary provided by Gardner and Lambert (1972) of over a decade’s worth of research. Their theory, according to Dornyei, has sparked a vast amount of research, being the most extensive investigation into the influence of attitudes and motivation on second language learning. Their studies primarily focused on English-speaking learners of French in North America. Findings from these studies indicate that learners who possess a stronger integrative orientation are more likely to attain higher proficiency levels. Skehan Afr Educ (1989: 53) emphasizes that this is a particularly critical source of motivation, as it is deeply connected to the learner’s personality.